Plate drift velocity controls on the levels of hydrocarbon source rock development taking the palaeozoic as an example - Yuan Zhuang; Fengli Yang; Mingchen Xu; Panpan Hu; Xin Liao (Scientific Reports)
Abstract Tectonic plate drift, a major force driving Earth’s geological history, governs the opening and closing of ocean basins, the breakup and assembly of supercontinents, and the formation of sedimentary basins. Recent geological, geophysical, and experimental evidence further suggests that plate drift velocity influences the geometry of slabs, the timing of large igneous province volcanism, and the chemical properties of oceanic rocks. While these studies have yielded significant academic insights, the direct impact of plate drift velocity on hydrocarbon resource development remains poorly understood, and relevant research is limited. This study is based on the latest Palaeozoic global plate reconstructions and previously published data on major Palaeozoic hydrocarbon source rocks. By comparing variations in the global plate drift velocity with the quantities and total organic carbon (TOC) contents of different types of hydrocarbon source rocks, we demonstrate the significant impact of plate drift velocity on hydrocarbon source rock development. Our results indicate that low plate drift velocities (0.97–5.00 cm/yr) provided the most favourable conditions for hydrocarbon source rock formation. Medium velocities (5.00–10.00 cm/yr) were moderately favourable, whereas high velocities (10.00–12.76 cm/yr) were relatively unfavourable. Furthermore, under low drift velocities, when plates were located at palaeolatitudes of 15–30°N/S and exhibited high stability, conditions were most conducive to high-abundance hydrocarbon source rock formation. These findings underscore the critical role of plate drift velocity in controlling hydrocarbon source rock development and provide a new perspective and approach for global hydrocarbon exploration and resource assessment.